Tryptophan deficiency and food intake depression in pigs : a thesis presented in partial fulfilment of the degree of Doctor of Philosophy in Animal Science at Massey University - Montgomery, Grant William (Massey University, 1976)
Two experiments are described, in which the effects or feeding pigs on a tryptophan deficient diet or supplemented diet were investigated. The feeding patterns of 10 cross-bred pigs were measured by continuous recordings of feed-bin weights, in a double reversal design experiment. The pigs, fed ad libitum, ate an average of 9 "meals" per day (range 5 - 16) with an average meal size of 170 g. There was a distinct diurnal pattern of food intake; most meals were eaten in the light phase of the day with peaks in the early morning and at midday and a large peak mid afternoon. Pigs fed the deficient diet showed some depression in food intake on the first day and the depression had reached maximal levels by the third day. On the deficient diet pigs ate 17 - 20% less than on the supplemented diet and most of the depression in intake was accounted for by reduced meal size. In the second experiment 4 pigs were trained to eat their daily ration in a 2 h period (0900 - 1100 h) and catheters were placed in the jugular veins. A double reversal experimental design was employed, with 3 periods of 5 days, and blood samples were taken over the feeding time on the second and fifth day in each period. The levels of plasma Glucose, Urea, Amino acids, Cortisol, Insulin, and Growth Hormone were measured. There were no significant differences between diets in levels of Growth Hormone or Cortisol. On day 2, Urea levels were higher in pigs fed the supplemented diet, while on day 5 there were no significant differences between diets. The lowered food intake on the deficient diet meant that both protein quality and protein intake were altered, which may explain the differences in Urea levels. The most consistent differences in plasma Amino acids levels occurred with tryptophan, the limiting amino acid, for which the levels were lower in pigs fed the deficient diet, although the differences were not statistically significant. Glucose rose higher in pigs fed the deficient diet and the differences could not be attributed to an altered Insulin response to feeding the deficient diet. It was concluded that the early changes in glucose and tryptophan may be associated with the food intake depression on the deficient diet, but further studies would be required before the relative importance of either relationship could be established.
Keywords: Pig diet; Tryptophan; Pig food intake